(untitled) (Al-Academy, 2023)
The topic of the research tagged (narrative structure and its impact on building open and closed endings in the fictional film) is summarized by studying the mechanism of employing closed and open endings in the fictional film. novelist, then the need for it, as well as the objectives of the research and clarifying its limits as well as its importance. Then moving to the theoretical framework, which included three topics, where the first topic was entitled (the cinematic construction of the film narrative), either the second topic (the structure of complexity and narrative solutions), or the third topic dealt with the subject (the structure of the end and its relationship to the construction of the narrative). After completing the theoretical aspect, the research concluded with a number of indicators of the theoretical framework that were adopted as a tool for analyzing the sample by analyzing the sample within the text of the theoretical framework, which is the movie (Legends of Autumn) directed by Edward Zwick, and the movie (The Legend of 1900) directed by Giuseppe Tornatori to come out With results and then conclusions and recommendations, then came the list of sources and footnotes in English.